The Alash Party: Historiography of the Movement - Saktaganova, Z.G.; Omarova, B.K.; Ilyassova, M.K.; Nurligenova, Z.N.; Abzhapparova, B.Zh; Zhalmurzina, A.Zh.; Mazhitova, Zh.S. (Space and Culture, India, 2020)
This research presents a short historiographical review of the Alash movement. It reflects the researchers’ own version of periodisation of the history of the first Kazakh national party Alash that belonged to the liberal democratic wing. The researchers identify four stages in the history of the movement connected with the main landmarks of its short, yet significant existence. The periods of Alash history are determined based on changes in strategy and tactics, as well as the evolution of its organisational forms (a movement— a party during elections to the Constituent Assembly — the ruling party in the Alash Autonomy and Alash Orda government). A conclusion is made that national parties set forth the conditions and ways of modernisation in the most acceptable forms and combinations for each corresponding nation; possible parallels in the development pathways followed by other national parties in 1918–1920 are pointed out.
Keywords: history of Kazakhstan in the 20th Century; soviet history; political parties of Kazakhstan; Alash; Alash Orda; stages in the history of the Alash party